A Perspective on Objective Measurement of the Perceived Challenge of Walking - Chatterjee, Sudeshna A.; Rose, Dorian K.; Porges, Eric C.; Otzel, Dana M.; Clark, David J. (Frontiers in Human Neuroscience, 2019)
Perceived challenge of walking is a broad term that we use to encompass walking-related anxiety, balance self-efficacy/confidence, and fear of falling. Evidence shows that even after accounting for physical performance capabilities, a higher perceived challenge can cause individuals to self-impose restrictions in walking-related activities. Perceived challenge is typically measured by self-report, which is susceptible to subjective measurement bias and error. We assert that measurement of perceived challenge can be enhanced by augmenting self-report with objective, physiologically based measures. A promising approach that has emerged in the literature is measurement of sympathetic nervous system (SNS) activity by recording skin conductance. Heightened SNS activity is a physiological stress response to conditions that are cognitively, emotionally, or physically challenging. In the present article we explain the rationale and physiological basis for measuring SNS activity to assess perceived challenge of walking. We also present existing and new evidence supporting the feasibility of this approach for assessing perceived challenge in lab-based and real-world walking environments. Future research directions are also discussed.